SOLID LIPID NANOPARTICLES AS DRUG DELIVERY SYSTEM - VISHVAJIT A. KAMBLE; DEEPALI M. JAGDALE; VILASRAO J. KADAM (International Journal of Pharma and Bio Sciences, 2010)
Solid lipid nanoparticles (SLNs) are alternative drug delivery system to colloidal drug delivery system such as liposome, lipid emulsions. SLNs are rapidly developing nanotechnology with several applications in drug delivery system, clinical medicine and other science. The ability of SLNs to incorporate drug into nanocarrier that offer new type in drug delivery system. Therefore SLNs is reaching the goal of controlled and site specific drug delivery system. In this article we discussed the preparation method, characterization, route of administration of SLNs, advantages, different preparation method which are suitable for large scale production and application of SLNs. Analytical techniques for characterization of SLNs like photon correlation spectroscopy, scanning electron microscopy, different scanning colorimetry are highlighted.